PREVENTION OF DNA SUGAR, HUMAN PERIPHERAL LYMPHOCYTES AND ERYTHROCYTES DAMAGES FROM FREE RADICAL INDUCED OXIDATION BY NATURAL ANTIOXIDANTS - NG, OMKAR; G, PREM KUMAR; V, BHAGYALAKSHMI; RAMADAS, DINESHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study focused on the identification of particular extract which shows signification protection of DNA sugar against excessive oxidation. Methods: The different extracts (water, alcohol, alcohol: water, and hexane) of Agathi seeds (Sesbania grandiflora Linn) were evaluated using various antioxidant and other relevant assays like DNA sugar protection and antioxidant activities. Results: The alcohol: water (1:1) extract of S. grandiflora Linn seeds showed the highest antioxidant and free radical scavenging activity. It inhibited membrane lipid peroxidation by 55% at 50 μg/ml, scavenged approximately 69% of hydroxyl and 1,1-diphenyl-2-picrylhydrazayl radicals at 2–3 fold lower concentrations compared to the other extracts. In addition, the alcohol: water extract inhibited ferrous sulfate: ascorbate-induced sugar oxidation of DNA and also showed non-toxic nature against lymphocytes. Conclusion: These results establish the antioxidant potential of the extract, which could be used as natural antioxidant source.